Glucokinase Gene Variants in the Common Form of NIDDM - Chiu, Ken C; Tanizawa, Yukio; Permutt, M Alan (Diabetes (New York, N.Y.), 1993)
To determine whether a structural defect in glucokinase could be a primary cause of glucose intolerance in the common form of NIDDM, the prevalence of mutations in the gene in 60 American black NIDDM patients was investigated. First, by Southern blot analysis of DNA from a subset of randomly selected subjects (n = 20), no gross deletions, insertions, or rearrangements of the gene were detected. Next, the 5′-untranslated and coding regions of the gene were amplified directly from genomic DNA by the polymerase chain reaction. PCR products were screened for mutations by using single-strand conformational polymorphism analysis. A total of nine variants were identified, with two in the 5′-UT regions of islet exon 1, two in the 5′-UT region of liver exon 1, and five in the coding regions. For islet exon 1, 5 of 60 NIDDM patients had both variants in the 5′-UT region; and for liver exon 1, two variants each occurred in 1 of 60 NIDDM patients. The coding region variants included a missense mutation in islet exon 1, substitution of Ala11 (GCC) with Thr11 (ACC), found in 2 patients. The biological consequences of this mutation and the mutations in the 5′-UT portion of the gene have yet to be determined. The rest of the variants were third base pair changes of codons, i.e., silent. A common polymorphism, which was in linkage equilibrium with microsatellite repeats GCK1 and GCK2, was found in intron 9, and a variant in intron 2 in both alleles of 1 patient. From these studies it was concluded that, although genetic variations in the coding sequence of the glucokinase gene are common, the amino acid sequence is highly conserved. The previous association of glucokinase alleles with NIDDM in American blacks has not been clarified by this analysis. Primary structural abnormalities of glucokinase do not play a significant role in the common form of NIDDM in this group.